2022
DOI: 10.14214/sf.10695
|View full text |Cite
|
Sign up to set email alerts
|

Estimating forest attributes in airborne laser scanning based inventory using calibrated predictions from external models

Abstract: Forest management inventories assisted by airborne laser scanner data rely on predictive models traditionally constructed and applied based on data from the same area of interest. However, forest attributes can also be predicted using models constructed with data external to where the model is applied, both temporal and geographically. When external models are used, many factors influence the predictions’ accuracy and may cause systematic errors. In this study, volume, stem number, and dominant height were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…The RMSE distributions in study I showed that with suitable sample plot combinations, scenario SN would provide even smaller RMSE values than the regional models (R). The observed benefit of the calibration plots is in line with findings of de Lera Garrido et al (2022). They concluded that 20 calibration plots would result in predictions comparable to the local models when spatially or temporally transferred models are applied to the target area.…”
Section: Als-based Models In Dipc-based Forest Inventories (Iii)supporting
confidence: 78%
See 2 more Smart Citations
“…The RMSE distributions in study I showed that with suitable sample plot combinations, scenario SN would provide even smaller RMSE values than the regional models (R). The observed benefit of the calibration plots is in line with findings of de Lera Garrido et al (2022). They concluded that 20 calibration plots would result in predictions comparable to the local models when spatially or temporally transferred models are applied to the target area.…”
Section: Als-based Models In Dipc-based Forest Inventories (Iii)supporting
confidence: 78%
“…They reported that model transfer to the target area performed best when the models were calibrated with a small number of sample plots from the target area. Use of calibration plots in the context of model transferability was also studied by de Lera Garrido et al (2022) in Norway. They calibrated temporally and spatially transferred models for volume, stem number and dominant height with a different number of local sample plots and concluded that calibration reduces the systematic errors.…”
Section: Prediction Of Forest Attributes Without New In-situ Field Me...mentioning
confidence: 99%
See 1 more Smart Citation